Implementing computerized technology: An organizational analysis. - Klein, Katherine J.; Conn, Amy Buhl; Sorra, Joann Speer (Journal of Applied Psychology, 2001)
Why do some organizations succeed and others fail in implementing the innovations they adopt? To begin to answer this question, the authors studied the implementation of manufacturing resource planning, an advanced computerized manufacturing technology, in 39 manufacturing plants (number of individual respondents = 1,219). The results of the plant-level analyses suggest that financial resource availability and management support for technology implementation engender high-quality implementation policies and practices and a strong climate for implementation, which in turn foster implementation effectiveness–that is, consistent and skilled technology use. Further research is needed to replicate and extend the findings.